Transformative Global Health Pedagogy: A Dinner Curriculum for Medical Students and Residents - Peter J. Frank; Katherine E. Schreck; Alexis Steinmetz; Erik S. Carlson; Conrad Stasieluk; Brian Borah; Hannah Reiser; Lucia Garcia; Ruth Kafensztok; Brian Medernach; Daniel Palazuelos (Association of American Medical Colleges, 2020)
Introduction The Hiatt Residency in Global Health Equity program at Brigham and Women's Hospital partnered with Loyola University Medical Center and the Stritch School of Medicine to build and share an innovative global health dinner curriculum (GHDC) based on the methodologies of transformative learning theory. This educational approach encourages trainees to critically analyze their frame of reference and has the potential to create practitioners equipped to advance health equity. Methods The GHDC explored broad global health (GH) topics through facilitated discussions with faculty and an experienced guest discussant over dinner. Medical students and internal medicine residents attended sessions based on their availability and interest. Participants completed surveys before and after every dinner. Comprehensive post-curriculum surveys were collected after participants had been involved for at least 1 year. Results In 2017-2018, 98% of the 37 participants preferred the dinner-style learning session to a didactic-style lecture (97% of the 37 participants in 2018-2019). Eighty-five percent (2017-2018) agreed or strongly agreed that dinners provided them with new knowledge on a GH topic (92% in 2018-2019). Seventy-two percent (2017-2018) agreed that the dinner introduced them to a new potential mentor in GH (66% in 2018-2019). Discussion The GHDC has been particularly successful in introducing participants to unfamiliar areas of medicine and new mentors. A second strength is its accessibility to medical students and residents. Its dependence on local resources allows versatility and customization; however, this trait also makes it difficult to prepackage the curriculum for interested institutions.